Targeting mechanisms of tailed bacteriophages. Issue 12 (December 2018) - Nobrega, Franklin; Vlot, Marnix; Jonge, Patrick; Dreesens, Lisa; Beaumont, Hubertus; Lavigne, Rob; Dutilh, Bas; Brouns, Stan
Abstract Phages differ substantially in the bacterial hosts that they infect. Their host range is determined by the specific structures that they use to target bacterial cells. Tailed phages use a broad range of receptor-binding proteins, such as tail fibres, tail spikes and the central tail spike, to target their cognate bacterial cell surface receptors. Recent technical advances and new structure–function insights have begun to unravel the molecular mechanisms and temporal dynamics that govern these interactions. Here, we review the current understanding of the targeting machinery and mechanisms of tailed phages. These new insights and approaches pave the way for the application of phages in medicine and biotechnology and enable deeper understanding of their ecology and evolution. Many phages use tails to attach to and penetrate the cell envelope of their bacterial hosts. In this Review, Brouns and colleagues explore recent structural and mechanistic insights into the interaction of phage tails with receptors on the bacterial surface.